Temperature effect of liquid crystal in photonic bandgap fiber-based Sagnac loop - Zhang, Yifan (2013)
Temperature effect of liquid crystal in photonic bandgap fiber (PBGF) based Sagnac loop was investigated. It shows that the longer length of the liquid crystal in the PBGF, the spectrum shifts more when the same degree of temperature changes. A total red-shifting of 6.44 nm was observed for liquid crystal length of 66 mm when the ambient temperature was increased of 22 °C, whereas only 1.3 nm was observed for the length of 1 mm.